2015
DOI: 10.1039/c4ra15123b
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the solvation of glucose in water, dimethyl sulfoxide (DMSO), tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) and its possible implications on the conversion of glucose to platform chemicals

Abstract: Cellulosic biomass derived molecules such as glucose can be converted into specific platform chemicals like 5-hydroxymethylfurfural (HMF), levulinic acid and gamma valerolactone (GVL). The solvation medium plays an important role in the selective conversion of glucose to these platform chemicals and it is shown that the addition of co-solvents increases the selectivity towards desired products and minimizes the formation of undesired condensation/polymerization products and humins. Hence, it becomes imperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 49 publications
1
89
0
Order By: Relevance
“…Biomass liquefaction reactions typically involve the liquid‐phase deconstruction of biomass to small organic oxygenates at temperatures between 200 and 380 °C . In these processes, organic solvents can be used to improve and accelerate lignin dissolution and to affect cellulose crystallinity, thus decreasing the amount of solid residues formed .…”
Section: Brief Summary Of Biomass Conversion Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass liquefaction reactions typically involve the liquid‐phase deconstruction of biomass to small organic oxygenates at temperatures between 200 and 380 °C . In these processes, organic solvents can be used to improve and accelerate lignin dissolution and to affect cellulose crystallinity, thus decreasing the amount of solid residues formed .…”
Section: Brief Summary Of Biomass Conversion Processesmentioning
confidence: 99%
“…Vasudevan et al. found that, with the presence of an organic solvent in water, the mobility of glucose molecules was reduced, forming longer‐lived hydrogen bonds with decreasing water content (Table ) . This was attributed to the increased hydrogen‐bonding strength of glucose with water and with organic solvents in the presence of increasing amount of organic solvents.…”
Section: Solvent Effects On Chemical Thermodynamicsmentioning
confidence: 99%
“…Like homogeneous systems, solvent selection is also of particular importance to determine the kind of final product. Some authors even claim that the solvent choice has a more important role in the selectivity of reactions than the working temperature and / or the chosen catalyst because the solvation medium is a key parameter that determines final yields, selectivity, activation energy, and reaction kinetics . A large number of solvents can be used in these catalytic reactions: Polar aprotic solvents, which are molecules with electric dipole or a multipole moment, which do not have a hydrogen atom bound to an oxygen or a nitrogen, but are generally double‐bounded to a carbon atom, like DMSO, dimethylformamide (DMF), dimethylacetamide (DMA), tetrahydrofuran (THF), ethyl acetate, dioxane, gamma‐valerolactone (GVL), and acetonitrile (ACN) …”
Section: La Production By Heterogeneous Reactionmentioning
confidence: 99%
“…Dimethylsulfoxide is widely used to produce HMF because it improves the selectivity of the reaction . Since water protonation is non‐selective, water forms hydrogen bonds with oxygen and hydrogen atoms of the OH in polysaccharides, whilst other organic solvents (such as DMSO, THF, or DMF) do it only with the hydrogen atoms, increasing final HMF yields (see Table ) . Several authors even report that, when using fructose / sulfated zirconia system, final HMF yields of 65.6% and 29.9 were obtained in acetone‐DMSO and water, respectively .…”
Section: La Production By Heterogeneous Reactionmentioning
confidence: 99%
See 1 more Smart Citation